2010
DOI: 10.1002/ange.200906079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Ruthenium(III)/NAMI‐A Adduct with Bovine Serum Albumin that Exhibits a High Anti‐Metastatic Activity

Abstract: Ru‐ndum erneuert: Röntgenabsorptionsspektroskopische Studien belegen, dass der RuIII‐Wirkstoff NAMI‐A alle seine Cl−‐ und S‐Donor‐Liganden gegen N‐Donoren und Carboxylatogruppen von Rinderserumalbumin (BSA) austauschen kann (siehe Schema). Das RuIII‐BSA‐Addukt verstärkt Zell‐Substrat‐Wechselwirkungen ebenso stark wie NAMI‐A (das sich im Zellkulturmedium binnen Minuten in RuIII‐BSA umwandelt).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Previous results demonstrated that HSA has the ability to improve the cytotoxicity and targeting of ruthenium compounds to some cancer cells [32,33,39]. Our experiments corroborate these findings.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Previous results demonstrated that HSA has the ability to improve the cytotoxicity and targeting of ruthenium compounds to some cancer cells [32,33,39]. Our experiments corroborate these findings.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, a doxorubicin prodrug, which exploits endogenous serum albumin as a drug carrier, also shows a superior antitumor effect on murine renal cell carcinoma in vivo [31]. The current research demonstrates that tethering an organometallic ruthenium-arene anticancer compound to HSA effectively improves targeting and anti-metastatic activity [32,33].…”
Section: Introductionmentioning
confidence: 83%
“…For example, while HEWL seems to protect the integrity of NAMI‐A, hCAII and cyt c favor its degradation. X‐ray absorption spectroscopy (XAS) studies showed that the coordination environment of the Ru III center in an NAMI‐A/serum albumin adduct is very different from that of the parent complex 26. Similar differences in the reactivity pathways of metal complexes depending on the selected protein have also been reported for other metallodrugs 2933.…”
mentioning
confidence: 70%
“…Indeed, a number of proteins, such as integrins, collagen and various proteases, were claimed as likely targets for this ruthenium(III) complex. Moreover, recently reported studies on the reactivity of NAMI‐A with serum albumin revealed that NAMI‐A/serum albumin adducts retain significant biological activity 26. Interestingly, the imidazole transfer from NAMI‐A to the catalytic Zn ion of hCAII is another aspect of the observed reactivity that could be further explored.…”
mentioning
confidence: 99%
“…Comparative analysis of the Cl K-edge XAS spectra of 13 and 13 /BSA revealed that the Cl environment is greatly perturbed upon protein binding. In a subsequent study of Liu et al 44 the binding behavior of 13 to BSA was analyzed by fitting a series of model compounds with known coordination to the unknown Ru(III)-BSA spectrum. The coordination environment of the adduct turned out to be completely different from that of the parent complex 13 with about 60% N and 40% O ligands coordinated to the Ru(III) center.…”
Section: Introductionmentioning
confidence: 99%